THE RISE OF ASIAN THESIS A Prediction of the Future Based on Changes in Centennial Balances and Parameters in the Global Conjuncture - Kurtbaş, İhsan (Fırat University, 2023)
While the nineteenth century is known as the English Century and the twentieth century as the American Century, the 21st century we live in is called the Chinese Century, the Asian Century, the Pacific Century, the Pacific Age, and the Asia Pacific Century. The bipolar world order under the domination of the USA and the USSR, which was established with the Cold War Era after the Second World War; With the collapse of the Soviet Union, it was replaced by a unipolar world order under the leadership of the USA. However, since the beginning of the 2000s, the balance of power in the world in economic, commercial and political terms has been changing in favor of Asia; A strong argument expressed as "the rise of Asia" has been voiced by wide circles. These Asian-centered macro developments, which point to a change and transformation on a global scale, mean the end of Western domination, which lasted for hundreds of years and identified with imperialism, hegemony and colonialism, or, with a more moderate approach, curbing the West with new balances of power. In the light of this argument, this study aims to present a future projection about and a comparative analysis of the current and future situations of the two poles centered in Asia and the West, in the light of parameters such as countries' GDP ratios, global import and export amounts, military power and defense expenditures, population ratios, and cross-cutting thematic issues. The data obtained show that the thesis of the rise of Asia, which refers to the majority of the continental states, especially the People's Republic of China, is an emerging theory unless there are extraordinary developments.

On dokuzuncu yüzyıl İngiliz Yüzyılı, yirminci yüzyıl Amerikan Yüzyılı olarak değerlendirilirken yaşadığımız 21. yüzyıl ise Çin Yüzyılı, Asya Yüzyılı, Pasifik Yüzyılı, Pasifik Çağı, Asya Pasifik Yüzyılı gibi isimlerle anılmaktadır. İkinci Dünya Savaşı sonrasında Soğuk Savaş Dönemi’yle tesis edilen ABD ve SSCB egemenliğindeki iki kutuplu dünya düzeni; Sovyetler Birliği’nin dağılmasıyla yerini ABD önderliğinde tek kutuplu dünya düzenine bırakmıştır. Bununla birlikte 2000’li yılların başından beri ekonomik, ticari ve siyasi açılardan dünyadaki güç dengeleri Asya lehine değişmekte; “Asya’nın yükselişi” şeklinde ifade bulan güçlü bir argüman, geniş çevreler tarafından dile getirilmektedir. Küresel ölçekte değişim ve dönüşüme işaret eden Asya merkezli bu makro gelişmeler, yüzlerce yıl süren ve emperyalizm, hegemonya ve sömürgecilikle özdeşleşen Batı egemenliğinin sonra ermesi veya daha ılımlı yaklaşımla Batının yeni güç dengeleriyle frenlenmesi anlamına gelmektedir. Bu argüman ışığında, bu çalışmada ülkelerin GSYH oranları, küresel ithalat ihracat miktarları, askerî güçleri, savunma harcamaları, nüfus oranları gibi parametreler ve kesişen tematik mevzular ışığında, Asya ve Batı merkezli iki kutbun mevcut ve gelecekteki durumlarının karşılaştırmalı analizi yapılarak; gelecek projeksiyonu ortaya konulmaya çalışılmıştır. Elde edilen veriler, olağanüstü gelişmeler olmadığı sürece, başta Çin Halk Cumhuriyeti olmak üzere, kıta devletlerinin büyük çoğunluğunu kast eden Asya’nın yükselişi tezinin gerçekleşmekte olan bir teori olduğunu göstermektedir.
ASYA’NIN YÜKSELİŞİ TEZİ KÜRESEL KONJONKTÜRDE DEĞİŞEN ASIRLIK DENGELER VE PARAMETRELER IŞIĞINDA BİR GELECEK PROJEKSİYONU